A Comparison of Convective Raindrop Size Distributions in the Eyewall and Spiral Rainbands of Typhoon Lekima (2019) - Bao, Xuwei; Wu, Liguang; Zhang, Shuai; Yuan, Huizhen; Wang, Huihui (Geophysical research letters, 2020)
A reliable shape–slope (μ‐Λ) relationship for polarimetric retrieval in tropical cyclones (TCs) is unavailable due to the lack of raindrop size distribution (RSD) measurements within the TC eyewall. This study presents an analysis of the convective RSDs in the eyewall and spiral rainbands, based on ~26 hr of measurement from 17 Thies disdrometers during the landfall of Typhoon Lekima (2019) in eastern China. A μ‐Λ relationship for polarimetric retrieval in the eyewall is derived, which is different from those in spiral rainbands of Lekima. The average raindrop diameter parameter Dm (concentration parameter log10Nw) is found to generally decrease (increase) radially from the TC center, but note that most rain samples with intense rain rate >50 mm hr−1 occur in the convection‐dominated portion of inner rainbands. To explain why, an equilibrium RSD is proposed as a constraint on the growth of Dm and log10Nw with increasing rain rate. Key Points A different convective RSD along with shape‐slope (μ‐Λ) relationship is found in the eyewall and various spiral rainbands of Lekima The average raindrop diameter Dm generally decreases radially from the TC center, whereas the average concentration log10Nw increases Most rain samples with an intense rain rate >50 mm hr−1 are concentrated in the convection‐dominated portion of inner rainbands